Analysis of Yield Gaps in cocoon production: A Cross Sectional Study in Jammu District - Ravi Kant; Muzamil Fayaz Rather; Jyoti Thakur (Public Health, 2026)
The study on the yield gaps in cocoon production was taken up at farmer’s level in Jammu district of Jammu & Kashmir UT. A total of 210 samples were drawn from three districts under study at random. The magnitudes of yield gaps were quantified and the possible reasons for such existence were reported. In the case of cocoon yield production, the gap was high in the local adopted group as compared to recommended/control group which was mainly due to higher adoption of recommended technologies and better allocation of resources. The study suggests that extension agents should educate the marginal farmers on the importance of adoption of recommended sericulture technologies to get higher benefits in sericulture.